2016
DOI: 10.1111/jgs.14368
|View full text |Cite
|
Sign up to set email alerts
|

Afternoon Napping and Cognition in Chinese Older Adults: Findings from the China Health and Retirement Longitudinal Study Baseline Assessment

Abstract: OBJECTIVES: To examine the cross-sectional associations between self-reported postlunch napping and structured cognitive assessments in Chinese older adults. DESIGN: Cross-sectional cohort study. SETTING: China. PARTICIPANTS: Individuals aged 65 and older from the baseline national wave of the China Health and Retirement Longitudinal Study (CHARLS) (N = 2,974). MEASUREMENTS: Interview-based cognitive assessments of orientation and attention, episodic memory, visuospatial abilities, and a combined global cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
170
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(178 citation statements)
references
References 37 publications
8
170
0
Order By: Relevance
“…However, conflicting findings may be due to measurement differences. For instance, a UK‐based study found napping to be protective with respect to cognitive decline, but only included older adults who were cognitively unimpaired at baseline and did not examine napping intention or frequency; other studies in China only assessed afternoon (ie, post‐lunch) nap duration …”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting findings may be due to measurement differences. For instance, a UK‐based study found napping to be protective with respect to cognitive decline, but only included older adults who were cognitively unimpaired at baseline and did not examine napping intention or frequency; other studies in China only assessed afternoon (ie, post‐lunch) nap duration …”
Section: Discussionmentioning
confidence: 99%
“…Episodic memory of cognition was tested using word recall of ten words . A list of 10 Chinese words was read to the respondents by the interviewer.…”
Section: Methodsmentioning
confidence: 99%
“…The intactness of mental status was assessed using 10 questions from TICS: today's date (month, day and year), day of the week, season of the year and serial subtraction of seven from 100 (up to five times) . The TICS score was calculated as the sum of correct answers for these 10 questions, which ranged from 0 to 10.…”
Section: Methodsmentioning
confidence: 99%
“…The word‐recall test was the average of the numbers of correct answers for immediate word recall and delayed recall from a list of 10 Chinese nouns, ranging from 0 to 10. The figure‐drawing test assessed the respondent's visual and spatial abilities . The respondents were shown a picture of two overlapped pentagons and asked to replicate the picture in a drawing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation